The social side of software platform ecosystems - DA SOUZA, Cleidson R. B. (Institutional Knowledge at Singapore Management University, 2016)
Software ecosystems as a paradigm for large-scale software development encompass a complex mix of technical, business, and social aspects. While significant research has been conducted to understand both the technical and business aspects, the social aspects of software ecosystems are less well understood. To close this gap, this paper presents the results of an empirical study aimed at understanding the influence of social aspects on developers’ participation in software ecosystems. We conducted 25 interviews with mobile software developers and an online survey with 83 respondents from the mobile software development community. Our results point out a complex social system based on continued interaction and mutual support between different actors, including developers, friends, end users, developers from large companies, and online communities. These findings highlight the importance of social aspects in the sustainability of software ecosystems both during the initial adoption phase as well as for long-term permanence of developers.